Legal Protection Of Intellectual Property Rights In Global Business - Budiman Budiman; Roberth Kurniawan Ruslak Hammar (Green Publisher Indonesia, 2024)
Intellectual property rights (IPR) are an important asset for business people, both individu-als and companies. IPR can protect intellectual works, such as copyrighted works, patents, brands and industrial designs. The aim of this research is to analyze the legal protection of IPR in global business. This research uses normative legal research methods. Research data was obtained through literature study. Research data was analyzed qualitatively in three stages, namely data reduction, data presentation and conclusion drawing. The re-search results show that legal protection for intellectual property rights in global business has actually been regulated in various legal sources such as conventions, one of which is regulated by Article 27 (2) Universal Declaration of Human Rights, the TRIPS Agreement (Agreement on Trade-Related Aspects of Intellectual Property) convention. Rights), Berne Convention for the Protection of Literary and Artistic Works, and Paris Convention for the Protection of Industrial Property. This regulation shows that intellectual property rights are part of human rights that must be protected, respected and fulfilled by the government.